Identification of a novel HLA‐C allele, HLA‐C*07:477 in a Drung Chinese individual. (10th May 2016) - Wang, J.; Yao, F. Z.; Ji, X.; Zhu, X. M.; Su, P. C.
Abstract : HLA‐C*07:477 has one nonsynonymous nucleotide change from HLA‐C*07:02:01:01 in codon 176, exon 3 (AAG>GAG).